2021
DOI: 10.1186/s43162-021-00065-w
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting glycemic control among Egyptian people with diabetes attending primary health care facilities in Mansoura District

Abstract: Background Diabetes is a rapidly growing health problem worldwide. In 2019, the International Diabetes Federation (IDF) estimates that Egypt is the 9th country worldwide with about 8,850,400 cases and a prevalence of 15.2% in adults. By 2045, Egypt is expected to be the 7th country worldwide. Several factors affecting glycemic control are related to patients, physicians, and the infrastructure of primary health care facilities (PHCFs). The effect of health care infrastructure and resources is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 18 publications
2
10
2
Order By: Relevance
“…The study showed that the education, occupation, and smoking status of patients affected diabetic control. The study further reported factors affecting glycemic control, but these factors were related to the primary healthcare physicians, and they included rural residence, participation in diabetes training, older age, longer duration since starting to deal with diabetic patients, as well as the status of following the guidelines [ 1 ].…”
Section: Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The study showed that the education, occupation, and smoking status of patients affected diabetic control. The study further reported factors affecting glycemic control, but these factors were related to the primary healthcare physicians, and they included rural residence, participation in diabetes training, older age, longer duration since starting to deal with diabetic patients, as well as the status of following the guidelines [ 1 ].…”
Section: Reviewmentioning
confidence: 99%
“…Diabetes mellitus (DM) is a rapidly growing public health crisis globally with a huge burden of disease [1]. It is a prevalent metabolic disorder characterized by a deficiency in the secretion of insulin or in its effect or both [2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unavailability of medications in the public sector, insufficient care, and disparities of services contribute to patient flow to the private sector 47 . Nearly 60% of patients with T2DM are not assessed by a specialist in MENA and AFR, with PCPs being the main first‐line treating physician 152,153 . Absence of electronic medical records (EMRs) may hinder sharing of patients' status and current therapies, leading to duplication of T2DM and other concomitant therapies.…”
Section: Health System Levelmentioning
confidence: 99%
“… 47 Nearly 60% of patients with T2DM are not assessed by a specialist in MENA and AFR, with PCPs being the main first‐line treating physician. 152 , 153 Absence of electronic medical records (EMRs) may hinder sharing of patients' status and current therapies, leading to duplication of T2DM and other concomitant therapies. User resistance, lack of awareness, and gaps in strategic implementation are the common barriers for adopting EMRs in developing countries.…”
Section: Health System Levelmentioning
confidence: 99%